Implementasi Program Bantuan Pangan Non Tunai Di Desa Moutong Tengah Kecamatan Moutong Kabupaten Parigi Moutong - Ramadhani, Nia; Djaelangkara, Rizali; Mayusa, Askar (JPS: Journal of Publicness Studies, 2026)
This study aims to determine the Implementation of the Non-Cash Food Assistance Program in Moutong Tengah Village, Moutong District, Parigi Moutong Regency. This research method uses a descriptive qualitative approach. This study uses data collection techniques by means of observation, interviews, and documentation. The theory used is George C. Edward III, there are 4 (four) indicators namely Communication, Resources, Disposition and Bureaucratic Structure. The results of the study show that the Implementation of the Non-Cash Food Assistance Program in Moutong Tengah Village, Moutong District, Parigi Moutong Regency, When viewed from the Communication Indicator shows that there are still many people who do not know the Non-Cash Food Assistance Program, this is due to the delivery of information and socialization that is not yet comprehensive. The Resource Indicator shows the lack of human resources for the Non-Cash Food Assistance Program because Moutong Tengah Village does not have a person in charge of the Non-Cash Food Assistance Program and is only given responsibility to the Village operator. The Disposition Indicator or the attitude of the implementer shows that the attitude and responsibility are still not good from the implementer because they are not in accordance with their main duties and functions. Bureaucratic Structure Indicators indicate that Moutong Tengah Village lacks integration among employees and officials in carrying out their duties due to a lack of coordination